Understanding Edwin Thumboo - Sui, Singapore, Gwee Li (Asiatic: IIUM Journal of English Language and Literature, 2013)
Edwin Thumboo is arguably the most famous and powerful figure in Singaporean literature. He is also the most controversial, generating a broad range of responses to the meaning and value of his verse. Thumbooâ€™s poetry parallels not just the stages of his life but problematically also how Singapore has developed socio-politically. These inextricable aspects create the very possibility for conflicting readings, which essentially disagree over historical decisions, the role of art and the impact of Thumbooâ€™s career and character. Â Â Â My essay will look at the construction of the image of Thumboo and its relation to these differing outlooks. I shall consider the dimensions of his historical place, his artistic convictions, his status in literary and academic culture and his own personality. A different way of working with Thumboo â€“ without using him to frame Singaporean literature â€“ is also proposed. My wish is to be able to confront objectively where this major poetâ€™s legacy stands today.Â Â